Habilidades blandas y su incidencia en el rendimiento laboral de los trabajadores administrativos en Quevedo – ecuador año 2024 - Salazar Rodríguez, Mariuxi Liseth (2025)
This research project focused on the study of soft skills and their impact on the job performance of administrative workers in the Quevedo canton, Ecuador. The main objective was to evaluate the relationship between soft skills and job performance, identifying both employees' strengths and areas for improvement in this area. The methodology employed was quantitative, using a structured survey as a data collection instrument. The results showed a positive correlation between the development of soft skills—such as effective communication, teamwork, adaptability, and leadership—and improved job performance. It was found that employees with greater mastery of these competencies displayed greater efficiency, collaboration, and conflict resolution skills, which positively impacts organizational objectives. In conclusion, it was confirmed that strengthening soft skills represents a key factor in improving the performance of administrative workers. Therefore, a comprehensive training plan was proposed as a solution, designed based on the identified needs, to foster a more productive, collaborative, and adaptable work environment to meet current challenges. Likewise, public and private sector organizations in Quevedo were recommended to establish ongoing human talent development policies, understanding that organizational success depends not only on technical competencies but also on the personal and relational growth of their employees.